Proceedings of Light-Activated Tissue Regeneration and Therapy Conference - Waynant, Ronald; Tata, Darrell B.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2008)
The Proceedings of the Light-Activated Tissue Regeneration and Therapy Conference covers the latest advances in the field including measurements that help determine the mechanisms of light-activated tissue regeneration and therapy. It also covers light sources that include lasers, LEDs, two wavelength sources, broadband sources and the metrology and medical outcomes they produce. These proceedings offer a systematic approach to the field of Light-Activated Tissue Regeneration and Therapy covering theory, basic research and clinical studies. Topics covered by leading medical experts and researchers include extensive papers and coverage on such interesting topics as: Pain Wound healing Diabetes Cardiovascular and stroke repair Neuroscience / progenitor and stem cells Dental About the Editors: The Editor of the proceedings, Ronald W. Waynant Ph.D., is a Senior Optical Engineer with the Food and Drug Administration Center for Devices and Radiological Health in Silver Spring, MD, and an Adjunct Associate Professor with the Uniformed Services University in Bethesda, MD. He previously served as an Adjunct Professor of Electrical Engineering at Catholic University. Dr. Waynant previously served as the Editor-in-Chief of IEEE Circuits and Devices Magazine and is a Fellow of The American Institute of Medical and Biological Engineers, The IEEE, The Optical Society of America, and The American Society for Laser Surgery and Medicine. Darrell Tata, Ph.D. is a senior biophysicist working at the FDA on non-invasive therapeutics through the application of physical techniques of optical and near infra-red light on biological systems. His current research is in the applications of non-ionizing radiation in obtaining desired biological activation and therapeutic response in several serious human diseases / ailments, notably, malignant cancers, diabetes, and chronic pain. Dr. Tata has conducted research at the University of Illinois at Urbana-Champaign (Dept. of Physiology and Biophysics), Stanford University (Dept. of Radiation Oncology), University. of Vermont (Dept. of Pharmacology), and the Mayo Clinic (Dept. of Urology). .
Mechanisms -- Mechanisms -- Near-IR Picosecond Pulsed Laser Induced Suppression of Metabolic Activity in Malignant Human Brain Cancer: An In-Vitro Study -- Wound Healing -- Combined 660 and 880 nm Light Improves Healing of Recalcitrant Diabetic Ulcers -- Blue Light Photo-Destroys Methicillin Resistant Staphylococcus aureus (MRSA) In-Vitro -- Photobiomodulation for the Treatment of Retinal Injury and Retinal Degenerative Diseases -- Irradiation with 780 nm Diode Laser Attenuates Inflammatory Cytokines While Upregulating Nitric Oxide in LPS-Stimulated Macrophages: Implications for the Prevention of Aneurysm Progression -- New Aspects of Wound Healing -- Photodynamic Therapy -- An Introduction to Low-Level Light Therapy -- Enhancing Photodynamic Effect Using Low-Level Light Therapy -- Light Fractionated ALA-PDT: From Pre-Clinical Models to Clinical Practice -- Combination Immunotherapy and Photodynamic Therapy for Cancer -- Patient-Specific Dosimetry for Photodynamic Therapy -- Novel Targeting and Activation Strategies for Photodynamic Therapy -- Cardiovascular -- Light Therapy for the Cardiovascular System -- Dentistry -- Introduction: Overview -- Optical Coherence Tomography Imaging for Evaluating the Photobiomodulation Effects on Tissue Regeneration in Periodontal Tissue -- Photobiomodulation Laser Strategies in Periodontal Therapy -- Combined New Technologies to Improve Dental Implant Success and Quantitative Ultrasound Evaluation of NIR-LED Photobiomodulation -- Photobiomodulation by Low Power Laser Irradiation Involves Activation of Latent TGF-?1 -- Diabetes -- The Role of Laser in Diabetes Management -- He-Ne Laser Irradiation Stimulates Proliferation and Migration of Diabetic Wounded Fibroblast Cells -- The Role of Colostrum Proline-Rich Polypeptides in Human Immunological and Neurological Health -- Neuroscience -- Phototherapy and Nerve Tissue Repair -- Laser Regeneration of Spine Discs Cartilage: Mechanism, In-Vivo Study and Clinical Applications -- FDA Regulations -- Requirements for FDA Approval -- Pain -- Pain Relief with Phototherapy: Session Overview -- Is Relief of Pain with Low-Level Laser Therapy (LLLT) a Clinical Manifestation of Laser-Induced Neural Inhibition? -- Complex Regional Pain Syndrome: A New Approach to Therapy -- Electric Field Interactions -- The Painful Derivation of the Refractive Index from Microscopical Considerations -- Independent Applications of Near-IR Broadband Light Source and Pulsed Electric Potential in the Suppression of Human Brain Cancer Metabolic Activity: An In-Vitro Study -- Electroencephalogram Changes Caused by Mobile Phones a Protective Device.
Keywords: Lasers; Photonics; Biomedical engineering; Biophysics; Biological physics; Medicine; Optics, Lasers, Photonics, Optical Devices; Biomedical Engineering and Bioengineering; Biological and Medical Physics, Biophysics; Biomedicine, general